BLENDED LEARNING BASED GOOGLE CLASSROOM USED TO IMPROVE THE STUDENTS’ READING COMPREHENSION - Muh Shofiyuddin; Sri Widya Ningsih; Olyvia Revalita Candraloka (Universitas Islam Nahdlatul Ulama Jepara, 2022)
This research aims to find out how effective of using blended learning trough Google Classroom application to improve the students’ reading comprehension. It is a True Experimental Design exactly Pretest-Posttest Control Design with 129 students as the population. Random sampling technique is used to decide the sample while reading test takes place as the instrument. The result of analyzing the data shows that the mean score of experimental group in pre-test 60.03 is lower than the mean score in post-test 81.91. While from the control group in pre-test 58.35 is lower than the mean score in post-test 62.06. The standard deviation of experimental group in pre-test is 19.719 and in post-test is 10.231 while from the control group in pre-test is 12.454 and in post-test is 14.311. From the computation of independent sample t-test in pre-test, the Sig. (2-tailed) is 0.686 which the level of significance is (0.686 > 0.05). It means that H0 is accepted and Ha is rejected. From post-test, the Sig. (2-tailed) is 0.000 which the significant level is (0.000 < 0.05). It shows that the use of blended learning through Google Classroom application is effective to improve the students’ reading comprehension at the eleventh grade students.